Theoretical and Practice Errors at Elementary Art Education - Helvacı, Ismail (Elsevier BV, 2012)
AbstractThis study explores teachers’ opinions in order to identify problems prevailing in Visual Arts courses in primary schools. This study is a qualitative one fulfilled by means of the interview method. The sampling of this study comprises 10 Visual Arts teachers working in elementary schools in the central province of Kastamonu. The surveyor employed interview questions developed by himself as a data collection tool. Among the survey findngs, some problems were observed in the Visual Arts courses in primary schools. Generally,those problems stem from mainly the policy of education, educational programmes, administrators, inadequacies of the environment and physical structure of schools in question.
Keywords: art teachers; art education; problem; primary schools; 4. Education